Influence of Ki impurity on spectral-kinetic properties of poly (9,9-di-n-octyl fluorenyl-2,7-diyl) films - Nurmakhanova, A.K.; Afanasyev, D.A.; Ibrayev, N.Kh. (Publishing House of the KarSU named after E.A.Buketov, 2017)
The spectral-fluorescent properties of the semiconductor films of poly (9,9 – di -n-octylfluorenyl- 2,7 - diyl) (PFO) doped with KI impurity have been investigated. The addition of the KI salt leads to a decrease in the degree of ordering of the PFO films. The complex nature of the dependence of the photoelectronic processes in the polymer on the impurity concentration KI is determined from an analysis of the values of the vibronic splitting, the Huang-Riesz factor, the concentration dependence of the intensity and lifetime of the PFO fluorescence. The addition of KI in the polymer leads to an increase in the concentration of excited triplet states in films. Analysis of the spectral-kinetic data of annihilation delayed fluorescence and phosphorescence indicates an increase in the disorder of polymer films with the addition of the KI salt.
Keywords: poly (9,9 – di -n-octylfluorenyl- 2,7 - diyl); KI salt; optical spectrum; fluorescence kinetics